2021
DOI: 10.3390/membranes11080551
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs as Promising Biomarkers to Evaluate ECMO Treatment Responses in ARDS Patients

Abstract: The use of extracorporeal membrane oxygenation (ECMO) for acute respiratory distress syndrome (ARDS) has increased in the last decade. However, mortality remains high, and the complexity of ECMO requires individualized treatment. There are some biomarkers to monitor progression and predict clinical outcomes of ARDS. This project aims to advance the management of ARDS patients treated with ECMO by exploring miRNA expression in whole blood. The analysis was conducted on two groups with different length of ECMO: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…An interesting review by Marchiori et al reviewed the current scientific literature about ECMO donors, focusing on the use of ECMO tissues as allografts [8]-a topic that will be probably become relevant in the next years. As an ideal conclusion of this chapter, two original studies focused on outcomes of ARDS patients supported by ECMO; Chiu [9] showed that propensity score-matched ARDS patients treated with ECMO are more likely to survive than patients on conventional protective mechanical ventilation, and this benefit seemed greater for the most severe patients and when the extracorporeal support was initiated early (i.e., within 48 h); Martucci and colleagues [10] defined a set of microRNAs which may provide new insights on the processes involved in the pathogenesis and evolution of ARDS and may represent promising biomarkers to evaluate ongoing treatments and for prognostication.…”
mentioning
confidence: 99%
“…An interesting review by Marchiori et al reviewed the current scientific literature about ECMO donors, focusing on the use of ECMO tissues as allografts [8]-a topic that will be probably become relevant in the next years. As an ideal conclusion of this chapter, two original studies focused on outcomes of ARDS patients supported by ECMO; Chiu [9] showed that propensity score-matched ARDS patients treated with ECMO are more likely to survive than patients on conventional protective mechanical ventilation, and this benefit seemed greater for the most severe patients and when the extracorporeal support was initiated early (i.e., within 48 h); Martucci and colleagues [10] defined a set of microRNAs which may provide new insights on the processes involved in the pathogenesis and evolution of ARDS and may represent promising biomarkers to evaluate ongoing treatments and for prognostication.…”
mentioning
confidence: 99%